ROLE OF NITRIC OXIDE IN DEVELOPMENT OF FIBROTIC CHANGES IN RATS’ TESTES AFTER 270 DAY CENTRAL DEPRIVATION OF TESTOSTERONE SYNTHESIS - Stetsuk, Ye.V.; Akimov, O.Ye.; Shepitko, K.V.; Boruta, N.V.; Goltsev, A.N. (World of Medicine and Biology, 2020)
Disturbance in production of nitric oxide (NO) may lead to various changes in different organs and systems. Certain clinical situations require prolonged usage of inhibitors of testosterone synthesis. Scientific literature provides limited information regarding the influence of prolonged deprivation of testosterone synthesis on production of NO and microscopic organization of rats’ testes. Prolonged central deprivation of testosterone synthesis leads to endothelial dysfunction, development of fibrosis, decreases the nitric oxide production and shifts pro-/antioxidant balance in favor of the pro-oxidants without increase in lipid peroxidation intensity. Central deprivation of testosterone synthesis leads to fibrosis with subsequent disruption of the structural organization of the convoluted seminiferous tubules, hemodynamic disturbances, endothelial dysfunction, increased density of the vascular wall of blood vessels and systemic stasis. Decreased production of NO from constitutive isoforms of NO-synthase plays major role in development of structural changes in the interstitial tissue of testes on the 270th day of the experiment.